IMAGE FORMING APPARATUS AND IMAGE FORMING METHOD USING THE SAME - OTOMURA NORIMICHI; KIHARA AKIKO; KURAUCHI TAKAHIRO (2023)
To provide an image forming apparatus that prevents a deterioration in cleanability and the occurrence of filming due to a long-term use and can provide stable, highly reliable images, and an image forming method using the same.SOLUTION: The above-mentioned problem is solved by an image forming apparatus comprising at least an electrophotographic photoreceptor, electrifying means, exposure means, developing means, and transfer means, wherein the electrophotographic photoreceptor includes at least a laminated photosensitive layer on a conductive support, wherein a charge transport layer contains at least a charge transport material, a binder resin, and fluororesin fine particles, and has a contact angle of its surface with pure water of 85° or more, and wherein a toner has a toner base particle that is externally added with at least two types of external additives: silica fine particles; and strontium titanate fine particles obtained by performing hydrophobic treatment, with a silane compound, on a surface of a core obtained by adding silica to strontium titanate.SELECTED DRAWING: Figure 1 【課題】長期使用によるクリーニング性の悪化およびフィルミングの発生がなく、安定した信頼性の高い画像を提供し得る画像形成装置およびそれを用いる画像形成方法を提供することを課題とする。【解決手段】電子写真感光体、帯電手段、露光手段、現像手段および転写手段とを少なくとも備え、電子写真感光体が導電性支持体上に積層型感光層を少なくとも備え、電荷輸送層が電荷輸送物質、バインダ樹脂およびフッ素系樹脂微粒子を少なくとも含有し、かつその表面の純水に対する接触角が８５°以上であり、トナーは、トナー母粒子がチタン酸ストロンチウムにシリカを添加したコアにシラン化合物で表面を疎水化処理したチタン酸ストロンチウム微粉体およびシリカ微粒子の、少なくとも２種の外添剤で外添されてなることを特徴とする画像形成装置により、上記の課題を解決する。【選択図】図１